Long‐term adverse effects and healthcare burden of rectal cancer radiotherapy: systematic review and meta‐analysis. Issue 1 (3rd October 2022) - Morton, Alastair J.; Rashid, Adil; Shim, Joanna S. C.; West, Joe; Humes, David J.; Grainge, Matthew J.
Abstract: Background: As rectal cancer survival increases, more patients survive with potentially severe, long‐term gastrointestinal and genitourinary complications from radiotherapy. The burden of these complications for patients and healthcare services is unclear, which this review aims to quantify. Methods: Systematic search of Medline and Embase for randomized‐controlled trials (RCTs) and multicentre observational studies published since 2000, reporting hospitalization/procedural intervention for long‐term (>6 months post‐treatment) gastrointestinal or genitourinary complications after radiotherapy and surgery for rectal cancer. Prevalence values were pooled in a meta‐analysis assuming random effects. Organ‐preservation patients were excluded. Results: 4044 records screened; 24 reports from 23 studies included (15 RCTs, 8 Observational), encompassing 15 438 patients. Twenty‐one studies (median follow‐up 60 months) reported gastrointestinal complications post‐radiotherapy: pooled prevalence 11% (95% confidence interval (95% CI) 8–14%). Thirteen reported small bowel obstruction: prevalence 9% (95% CI 6–12%), a 58% increased risk compared with surgery alone (RR 1.58, 95% CI 1.26–1.98, n  = 5 studies). Seven reported fistulas: prevalence 1% (95% CI 1–2%). Thirteen reported genitourinary complications: prevalence 4% (95% CI 1–6%); RR 1.10 (95% CI 0.88–1.38, n  = 3 studies) compared with surgery alone. Conclusions: Over 10% of patients are hospitalized for long‐term complications following rectal cancer radiotherapy. Serious gastrointestinal complications are commonplace; late small bowel obstruction is more common in patients having radiotherapy and surgery compared with surgery alone. Patients and clinicians need to be aware of these risks. Abstract : The long‐term healthcare burden of complications after rectal cancer radiotherapy is unclear. This meta‐analysis demonstrates ~1 in 10 patients treated with radiotherapy will have a serious late gastrointestinal complication requiring hospital admission, more common than with surgery alone. Earlier diagnosis would reduce the need for radiotherapy and these complications.